Lectures on philosophy - Weil, Simone (Cambridge University Press, 1978)
Simone Weil's Lecons de Philosophie are derived from a course she taught at the lycee for girls at Roanne in 1933-4. Anne Reynaud-Guerithault was a pupil in the class; her notes are not a verbatim record but are a very full and, as far as one can judge, faithful rendering, often catching the unmistakable tone of Simone Weil's voice as well as the force and the directness of her thought. The lectures form a good general introduction to philosophy, ranging widely over problems about perception, mind, language, reasoning and problems in moral and political philosophy too. Her method of presentation is a characteristic combination of abstract argument, personal experience and literary or historical reference. Peter Winch points out in his introduction to the book some of the more systematic connections in her philosophical work (and between this philosophical work and her other concerns), and makes a number of suggestive comparisons between Simone Weil and Wittgenstein. The translation is by Hugh Price from the Plon edition of 1959. Dr Price has added some notes to explain references in the text that might be unfamiliar to English speaking students beginning philosophy.